(untitled) (Al-Academy, 2016)
Linked to the post-modern historical transformations sociological which raided the developed Western societies since the middle of last century, which consisted mainly in the emergence of what he called Alsosiologion (consumer society a) and (Affluent Society), as it appeared the new social lifestyle is not only characterized by the provision of the accumulation of capital and sparingly in spending, but rather a kind of extravagance and encourage consumption, prompting some to say that consumption is a community postmodern engine, and other labels for this period of economic backgrounds, such as the new capitalism and the system of the new capitalist Alseperntiqi technical and labels purist such as industrial post-society emerged, some also talked about community media or informational result of the evolution of the media and communication technologies and the acquisition of all of this information to urge the researcher to search for attributes this rich period. It summarized the research problem in the following question: What are the effects of the post-modern industrial design of civilization as a variable in all its aspects and the impact therefore on industrial product and its body?, And the importance of research has consisted b by subtracting the currents and schools ideas for this period Kmatherat and its importance in building industrial product and its development over a period of post-modernism.The search to identify the most important attributes of industrial design in the post-modern goal, also defines research study designs furniture as one of the industrial products for a period of post-modernism.The theoretical framework dealt with the following: the nature of postmodernism and when it started, and in the opinion of postmodern theorists and most important industrial design features of the post-modern, while the most important findings of the research are:- A period marked by postmodern combination of previous models and used in the.body design of industrial products